Science and technology in world history : an introduction - McClellan, James E., III (James Edward), 1946-; Dorn, Harold, 1928- (Baltimore : Johns Hopkins University Press, 2015)
Facts and figures have been thoroughly updated and the work includes a comprehensive Guide to Resources, incorporating the major published literature along with a vetted list of websites and Internet resources for students and lay readers.
PrefaceIntroductionPart I.1. Humankind Emerges2. The Reign of the Farmer3. Pharaohs and Engineers4. Greeks Bearing Gifts5. Alexandria and AfterPart II.6. The Enduring East7. The Middle Kingdom8. Indus, Ganges, and Beyond9. The New WorldPart III.10. Plows, Stirrups, Guns, and Plagues11. Copernicus Incites a Revolution12. The Crime and Punishment of Galileo Galilei13. "God said, 'Let Newton be!'"Part IV.14. Textiles, Timber, Coal, and Steam15. Legacies of Revolution: From Newton toEinstein16. Life Itself17. Toolmakers Take Command18. The New Aristotelians19. The Bomb, the Internet, and the Genome20. Under Today's Pharaohs Afterword Guide to Resources Illustration Credits Index.
Includes bibliographical references and index.
ENH
Hye trade International
Keywords: Science -- History; Technology -- History; Tool and die makers -- History; English language